Strategy for Improving the Quality of Employee Work: Analysis of Training Implementation, Career Development and Team Work - Wenny Desty Febrian (Greenation International Journal of Economics and Accounting, 2023)
The strategy article for improving employee work quality: Analysis of training implementation, career development and team work is a scientific literature review article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of influence between variables which can later be used for further research within the scope of human resource management science. The research method used is descriptive qualitative. Data was obtained from previous studies relevant to this research and sourced from academic online media such as publish or perish, google scholar, garba digital reference and journal sinta. The results of this article are: 1) Training has an effect on improving the quality of employee work; 2) Career development has an effect on improving the quality of employee work; and 3) Team work has an effect on improving the quality of employee work.